Mixed-phase bismuth ferrite thin films by chemical solution deposition. Issue 11 (7th March 2018) - Zhang, Qi; Huang, Hsin-Hui; Sando, Daniel; Summers, Max; Munroe, Paul; Standard, Owen; Valanoor, Nagarajan
Abstract : Epitaxial mixed-phase BFO//LAO thin films with enhanced electromechanical performance were successfully synthesized by chemical solution deposition. Abstract : Epitaxial mixed-phase bismuth ferrite (BiFeO3, BFO) thin films were successfully synthesized on (001) lanthanum aluminate (LaAlO3, LAO) substrates by a chemical solution deposition (CSD) technique. X-ray diffraction measurements confirm the co-existence of a completely relaxed rhombohedral-like (R′) phase and a strained tetragonal-like (T′) phase. Atomic resolution scanning transmission electron microscopy (STEM) measurements reveal that the T′ and R′ phases in our CSD derived BFO/LAO films are mixed homogeneously at the nanoscale. This is in stark contrast to the typical physical vapor deposition derived mixed-phase BFO thin films, which show R′ phase striations embedded in a T′ phase matrix. This phenomenon is attributed to the specific deposition-nucleation-crystallization-relaxation pathway characteristic of the CSD route. This homogenously mixed-phase still demonstrates the well-known morphotropic phase boundary effect, i.e. superior electromechanical properties compared to either the pure T′ phase or R′ phase constituents themselves. Moreover, the maximum piezoelectric coefficient measured by using nanoscale top electrodes shows surprising insensitivity to the clamping effect from the substrate, thereby offering considerable promise in thin film applications.